Accuracy of Urine Cytology In Detecting Bladder Cancer - Ahlan Syahreza; Ferry Safriadi (Majalah Kedokteran Bandung, 2021)
One of the most prevalent and deadly cancers in men is bladder cancer. To achieve the best possible outcome, physicians need to diagnose it promptly. The gold standard for diagnosis is tissue biopsy, but this method is invasive. There is another option for non-invasive diagnostic using urine cytology. The purpose of this study was to measure the accuracy of urine cytology in diagnosed bladder cancer patients. This study extracted data from patients medical records in a tertiary hospital in Indonesia from 2009–2019. The diagnostic accuracy was then compared between urine cytology and biopsy as the gold standard. Data on subjects’ baseline characteristics and diagnostic accuracy (sensitivity, specificity, PPV, and NPV) were collected. Results were then stratified according to the American Joint Committee on Cancer pathology staging for bladder cancer. Of 124 study subjects, male was more dominant (male,88% versus female, 12%) Seventy-five patients had a T1-tumor stage. Overall, the diagnostic accuracy was as follows:sensitivity, 47.8%; specificity, 90.9%; PPV, 98.2%; and NPV, 14.5%. High-grade tumors were shown to have a higher sensitivity. The highest accuracy was found in the MIBC grade T3, which was 90.68%. For diagnostic accuracy, urine cytology offered high specificity, but low sensitivity. The exploration of other markers is needed to establish a non-invasive but accurate method to diagnose bladder cancer.